Desert pisciculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Highly saline ponds fed by underground water, commonly found under deserts, could produce 100,000 kg of fish per hectare. New techniques developed at Tel Aviv University in Israel are showing that desert communities could use such ponds as new...